PENERAPAN MEDIA GAME WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV MI AL – MAWASIR KABUPATEN LUWU - Indarwati; M. Zulham; Iin Dwi Aristy Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of students at MI AL-Mawasir in Indonesian language lessons, especially vocabulary. The purpose of this study is to describe the application of Wordwall game media to improve the learning outcomes of fourth-grade students of MI AL-Mawasir, Luwu Regency. This type of research is classroom action research (CAR) using the Kemmis & Mc Tanggart model which consists of two cycles consisting of four stages: planning, implementation and observation and reflection. The subjects in this study were 18 fourth-grade students of MI AL-Mawasir in the 2025/2026 academic year, consisting of 9 boys and 9 girls. Data collection techniques used were observation and tests. The results of this study indicate that the application of Wordwall game media is able to improve student learning outcomes in learning Indonesian vocabulary material, namely prepositions and adjectives. The results of this study indicate an increase in student learning outcomes after the application of Wordwall game media. In the pre-cycle, learning completeness only reached 44%. After the implementation of cycle I, learning completeness reached 50%, and in cycle II it increased to 83%. In cycle I, the average student score was 70, and still had not reached the KKTP score of 75. In cycle II, there was an increase with an average score of 82. Thus, the application of Wordwall game media can effectively improve the Indonesian language learning outcomes of fourth grade students of MI AL-Mawasir, Luwu Regency, on the material of prepositions and adjectives, showing an increase through the application of Wordwall game media.